The Role and Political Communication Through Literature of Major General Luang Wichitwathakan: A Study for the Period of B.E. 2481-2505 - Apithanakoon, Krongphon; Srisoontorn, Rassamee (Arts of Management Journal, 2023)
This article examines the political context from 1938 to 1962 through the works of Major General Luang Wichitwathakan, with a focus on how it affected political communication. The aim is to analyze the political communication process of Major General Luang Wichitwathakan through literature. Qualitative research was conducted using Brian McNair's political communication model and David K. Berlo's S-M-C-R communication process elements. The research findings found that: 1. Luang Wichitwathakarn played an important political role in the government of Field Marshal P. Pibulsongkhram, using historical plays to introduce the concept of "Nationalism" to the public. Luang Wichitwat's writings and plays reflect his beliefs and thoughts on nationalism. Many of his inspiring songs have endured the test of time and are still celebrated today. 2. The study conducted on the political communication process through the writings of Major General Luang Wichitwathakarn between the years B.E. 1938 and 1962 found that there were four key components to his writing. Firstly, Luang Wichitwathakarn, as the sender or messenger, played a vital role in creating values and cultivating nationalism. Secondly, he used historical scripts, names of cities, landscapes, and historical figures to connect the story and deliver his message. For instance, he used "Luet Suphan" to connect with the story. Thirdly, he used various literary works, such as Luet Suphan, Ratchamnu, King Krungthon, Battle of Thalang, Princess Saen Wee, etc., as channels to send his message. Finally, middle-class readers were the primary receivers of his message.